Resistência para um modo de existência : luta camponesa em defesa das sementes crioulas no semiárido alagoano - Santos, Flávio dos (2020)
In the context of peasant social reproduction, seeds are an essential element, as they are important organisms for agricultural activities carried out by these workers, a fact that provides the emergence of unique knowledge, materialized in planting, germinating, handling and harvest. As a result of this process, we highlight the so-called Creole seeds, organisms that have biological and cultural traits originated in peasant work, a pure seed, free from any improvement made in the laboratory, being passed on from generation to generation. Against this backdrop, seed business corporations have been intensifying the application of biotechnological packages in agriculture, in order to dominate world seed production. In the face of these attacks, peasants have been carrying out resistance actions in order to protect Creole organisms, a fact that also occurs in the semiarid region of Alagoas, where a process of struggle has been undertaken that materializes in the formation of a state network of Community Seed Banks, spaces custody of Creole seeds and political articulation. Having as methodological support the HistoricalDialectic Materialism and guided by a quantitative and qualitative approach, this dissertation research aimed to analyze the historical process of resistance carried out by the peasantry in the defense of Creole seeds in the semiarid of Alagoas (1980-present), in the context the advance of capitalist accumulation in the Brazilian field. The results of the research show that from the 1960s, with the modernization of agriculture, Brazil entered the tracks to become a great producer of commodities, a fact accomplished with the advent of the agribusiness economy, a movement that had as one of its faces the production of improved seeds in the laboratory: hybrid and transgenic, which, currently, are being disseminated in the Brazilian agrarian space with greater intensity. In the reality of Alagoas, we identified that this advance has occurred through public politics, as well as through sales in open markets and agricultural houses. Faced with this context, peasants have been expanding resistance strategies in order to safeguard Creole seeds, a process that takes place in a scenario of intensification of capitalist accumulation in the countryside, which is spatialized in the Alagoas Semiarid and, together with the actions of the State, has been potentiating the contradictions in space production, creating multiple challenges for the Community Seed Banks to continue writing their history of resistance.